Philosophical Content of Iris Murdoch’s Novel (Zien Journal of Social Sciences and Humanities, 2022)
This article is dedicated to the philosophical content of Murdoch's novels. The originality of Murdoch's artistic pursuits is directly related to her profession. For many years, the writer has been teaching a course in philosophy, primarily existentialism, at Oxford University. Teaching does not interfere with creativity: Murdoch is the author of more than thirty novels. She poses and solves moral and philosophical problems based on the material of private life, avoiding social and historical concreteness in the depiction of the characters' destinies and their inner appearance